2001
DOI: 10.1889/1.1831904
|View full text |Cite
|
Sign up to set email alerts
|

29.4L: Late‐News Paper: Image Synchronized Brightness Control

Abstract: A novel image synchronized brightness control (ISBC) method for active matrix liquid crystal display (AMLCD) was developed, where automatic modulation of the backlight luminance is performed according to the gray distribution of image data. The ISBC can deliver a peak luminance of 500 ~ 600 nits, which is very comparable to that of cathode ray tubes (CRTs) and is 2 to 3 times higher than that of normal LCD. The dynamic CR is over 700. With this ISBC method we can display a vivid moving image, while maintaining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…The backlight is typically updated globally once per frame while the LCD data is addressed in lines sequentially 1 . In this case, the backlight can be synchronized with at most one line.…”
Section: Backlight and Lcd Data Synchronizationmentioning
confidence: 99%
“…The backlight is typically updated globally once per frame while the LCD data is addressed in lines sequentially 1 . In this case, the backlight can be synchronized with at most one line.…”
Section: Backlight and Lcd Data Synchronizationmentioning
confidence: 99%
“…A dynamic backlight control algorithm, for example, was proposed to increase the dynamic contrast ratio of CRTs back to 2001 [1]. Backlight scaling is by far the most effective technique for reducing power consumption in a TFT-LCD monitor.…”
Section: Previous Work On Backlight Scalingmentioning
confidence: 99%
“…In literature, researchers have found that the display consumes a major portion of the total power consumption in portable devices, and proposed related low-power techniques [1]. The liquid crystal display (LCD) has been widely used in batterypowered portable electronics such as laptop computers, personal digital assistants, cell phones, global positioning systems, etc.…”
Section: Introductionmentioning
confidence: 99%
“…To save the power consumption of backlight for LCD and enhance the image contrast, some techniques on adaptive dimming have been introduced [3]- [9]. The adaptive dimming technique can be categorized into three classes: OD (uniform dimming or backlight scaling), 1D (line or channel dimming), and 2D (local dimming, block dimming, or cluster dimming).…”
mentioning
confidence: 99%
“…The adaptive dimming technique can be categorized into three classes: OD (uniform dimming or backlight scaling), 1D (line or channel dimming), and 2D (local dimming, block dimming, or cluster dimming). The backlight scaling method [3]- [6] dims the whole backlight luminance is reduced by a dimming factor k, and, at the same time, video signal is enhanced by a factor 11k, according to the input video signal when the peak luminance is low. Therefore, this method can reduce the backlight illumination with image processing to retain the image fidelity.…”
mentioning
confidence: 99%